The Evolution of Work from Home - José María Barrero; Nicholas Bloom; Steven J. Davis (Institute of Labor Economics (IZA), 2023)
Full days worked at home account for 28 percent of paid workdays among Americans 20-64 years old, as of mid 2023, according to the Survey of Working Arrangements and Attitudes. That's about four times the 2019 rate and ten times the rate in the mid-1990s that we estimate in time-use data. We first explain why the big shift to work from home has endured rather than reverting to pre-pandemic levels. We then consider how work-from-home rates vary by worker age, sex, education, parental status, industry and local population density, and why it is higher in the United States than other countries. We also discuss some implications of the big shift for pay, productivity, and the pace of innovation. Over the next five years, U.S. business executives anticipate modest increases in the share of fully remote jobs at their own companies and in the share of jobs with hybrid arrangements, whereby the employee splits the workweek between home and employer premises. Other factors that portend an enduring shift to work from home include the ongoing adaptation of managerial practices and further advances in technologies, products, and tools that support remote work.
Keywords: D13; D23; E24; J22; J31; M54; R3; 330; work from home; productivity; labor costs; job amenities; COVID-19